2012
DOI: 10.1093/ntr/nts215
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Social Behavior in Nicotinic Acetylcholine Receptor  4 Subunit-Null Mice

Abstract: introduction: Tobacco addiction has a strong social component. Therefore, nicotinic acetylcholine receptors (nAChR) may influence social behavior. Because the β4 nicotinic receptor subunit is important for possibly related behaviors, such as anxietylike behavior and the effects of nicotine, we studied the social behavior of mice null for the β4 nAChR subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In particular, the lack of β2 nAChR subtype was shown to affect social interaction during aggressive behavior ( Granon et al, 2003 ), an effect likely involving the medial prefrontal cortex (mPFC; Avale et al, 2011 ). The lack of β4 nAChR subunit that is highly expressed in the olfactory bulb and in the lateral habenula ( Salas et al, 2003 ), leads to a decreased interaction between a resident and juvenile intruder mouse ( Salas et al, 2013 ). Furthermore, a single nucleotide polymorphism in the α5 subunit of nAChRs, observed in patients affected by schizophrenia ( Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014 ), leads to deficits in sociability when engineered in mice ( Koukouli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the lack of β2 nAChR subtype was shown to affect social interaction during aggressive behavior ( Granon et al, 2003 ), an effect likely involving the medial prefrontal cortex (mPFC; Avale et al, 2011 ). The lack of β4 nAChR subunit that is highly expressed in the olfactory bulb and in the lateral habenula ( Salas et al, 2003 ), leads to a decreased interaction between a resident and juvenile intruder mouse ( Salas et al, 2013 ). Furthermore, a single nucleotide polymorphism in the α5 subunit of nAChRs, observed in patients affected by schizophrenia ( Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014 ), leads to deficits in sociability when engineered in mice ( Koukouli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social interactions of PD patients may be affected by disrupted social connectedness (Soleimani et al, 2014); PD patients with mild cognitive deficits showed impairment in social behavior (Anderson et al, 2013). As mentioned, nicotine and other nicotinic agonists activate several nAChR subtypes which are involved in social behavior in monkeys and rodents (Bitner et al, 2010; Boess et al, 2013; Feuerbach et al, 2009; Henderson and Lester, 2015; Salas et al, 2013; Sarter et al, 2009; Timmermann et al, 2012). Chronic nicotine treatment also benefited social behavior in G72Tg mice, a possible mouse model of schizophrenia (Hambsch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the PFC, nicotinic ACh receptors (nAChRs) have been described to play important roles in the modulation of social behaviours (Avale et al, 2011; Coura et al, 2013; Granon et al, 2003; Salas et al, 2013). Cholinergic signalling in the striatum has also been suggested to participate in the modulation of social preference (Karvat & Kimchi, 2014; Rapanelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite deficits in social memory and social preference being a significant health problem and burden on society, the role of neurochemical pathways in social behaviour is poorly understood. The central cholinergic system has been suggested to contribute to the regulation of social behaviour (Coura et al, 2013;Karvat & Kimchi, 2014;Lewis et al, 2015;Mineur et al, 2013;Prado et al, 2006;Salas et al, 2013;Van Kampen et al, 2004;Winslow & Camacho, 1995). Mice with decreased levels of acetylcholine (ACh) in the brain show decreased social interaction and impaired social memory, and these deficits can be relieved using acetylcholinesterase inhibitors (Prado et al, 2006).…”
Section: Introductionmentioning
confidence: 99%